2017
DOI: 10.1111/aji.12618
|View full text |Cite
|
Sign up to set email alerts
|

Human chorionic gonadotropin potentially affects pregnancy outcome in women with recurrent implantation failure by regulating the homing preference of regulatory T cells

Abstract: The results of this study provide novel evidence supporting a role of hCG in regulating the differentiation of peripheral FOXP3 Tregs. The alterations of circulating Tregs may positively affect the pregnancy outcomes of patients with a history of RIF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 39 publications
(60 reference statements)
3
37
0
Order By: Relevance
“…72 suggesting hCG not only mediates the chemotaxis of Tregs, but also enhances its immunosuppressive function. 74 We further observed that the percentage of CCR4 + Foxp3 + Tregs were significantly increased following the stimulation of naïve CD4 + T cells with hCG than those without hCG. 73 Our previous study also found that the percentages of endometrial Foxp3 + Tregs and peripheral CCR4 + Foxp3 + Tregs were significantly lower in the women with recurrent implantation failure as compared with those of healthy controls, suggesting a lack of endometrial Tregs may be detrimental to endometrial receptivity and embryo implantation.…”
Section: Nk Cellsmentioning
confidence: 58%
See 3 more Smart Citations
“…72 suggesting hCG not only mediates the chemotaxis of Tregs, but also enhances its immunosuppressive function. 74 We further observed that the percentage of CCR4 + Foxp3 + Tregs were significantly increased following the stimulation of naïve CD4 + T cells with hCG than those without hCG. 73 Our previous study also found that the percentages of endometrial Foxp3 + Tregs and peripheral CCR4 + Foxp3 + Tregs were significantly lower in the women with recurrent implantation failure as compared with those of healthy controls, suggesting a lack of endometrial Tregs may be detrimental to endometrial receptivity and embryo implantation.…”
Section: Nk Cellsmentioning
confidence: 58%
“…73 Our previous study also found that the percentages of endometrial Foxp3 + Tregs and peripheral CCR4 + Foxp3 + Tregs were significantly lower in the women with recurrent implantation failure as compared with those of healthy controls, suggesting a lack of endometrial Tregs may be detrimental to endometrial receptivity and embryo implantation. 74 We further observed that the percentage of CCR4 + Foxp3 + Tregs were significantly increased following the stimulation of naïve CD4 + T cells with hCG than those without hCG. 74 These evidences suggested that IUI-hCG might be a potential target therapy for patients with RPL and implantation failure lacking Tregs.…”
Section: Treg Cellsmentioning
confidence: 58%
See 2 more Smart Citations
“…In a recent study, Schumacher et al used migration assays to demonstrate that regulatory T cells (Treg) were attracted by HCG-producing trophoblasts [29]. More importantly, HCG was recently reported to be involved in Treg differentiation [30]. In addition, HCG was found to adjust the T helper (Th) 1/T helper (Th) 2 balance, since HCG inhibited the development of Th1 autoimmune diabetes in a mouse model [31].…”
Section: Human Chorionic Gonadotrophin (Hcg): the Role In Implantamentioning
confidence: 99%